Pendampingan Asuhan Pada Ibu Hamil dengan Herpes Zoster - Fauzi, Aulia; Putri, Kalisha Andriani; Kirana, Mega Adilah Cucu; Yulinar, Yayu; Solihah, Rosidah; Sandriani, Sandriani (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Pregnancy is a crucial phase in a woman's life, accompanied by various physiological and pathological changes. One of the challenges that may arise during pregnancy is infection, including viral infections such as herpes zoster. The intense pain caused by the condition, the risk of secondary infections, and the resulting anxiety can significantly impact the well-being of the mother. Moreover, limited knowledge about the disease among pregnant women often worsens their condition, both physically and emotionally. Providing educational midwifery care and support to pregnant women with herpes zoster is a strategic step to ensure they receive comprehensive and holistic care. Objective: The objective of this activity is to provide a solution to the challenges in delivering comprehensive care to pregnant women with herpes zoster, aiming to reduce maternal anxiety during pregnancy by increasing their knowledge related to the care provided. Method: The activity was carried out in three stages: problem identification and initial assessment, education and care support, and finally, evaluation and outcome measurement. Result: There was a significant improvement in knowledge following the educational intervention. Conclusion: Based on the assessment of the pregnant woman's knowledge about herpes zoster before and after the educational intervention, a significant increase was observed. Prior to the education, the mother's level of knowledge was categorized as low, with a score of 50.